Role and Importance of Schemas in Pedagogy and Learning: A Cognitive Approach - Naveed Akram Ansari (Journal of Communication and Cultural Trends, 2019)
Educational strategies are designed to cope with and fulfill the multifarious pedagogical and educational needs of teachers and learners. Moreover, no educational plan can possibly yield the required results without incorporating suitable instructive strategies. This research paper advocates the role and importance of schemas in learning new forms of knowledge and data in the perspective of class room teaching-learning. Cognitive approach is adopted to understand how students learn new forms of knowledge and experiences through different mental processes, quite unlike that of behaviorism. The concept of schema helps us understand how learners can link new pieces of information to the already existing knowledge in their minds. The notion of ‘Constructivist Approach’ has been extracted from the field of educational psychology for triangulation. Extracts are taken from the textbooks of English used in matriculation and intermediate through purposive sampling. Their analysis shows that schemas can play a vital role in enhancing the learning experience and making new forms of knowledge a permanent part of the memory of students which is the ultimate goal of education.